The Sistem Monitoring Pengukur Jarak Ketinggian Air pada Bendungan Berbasis Internet Of Things - Said, Syukroni; Samsumar, Lalu Delsi; Emi Suryadi; Ardiyallah Akbar; Zaenudin (Yayasan Nuraini Ibrahim Mandiri, 2024)
Technological advances continue to affect human life, but many water level measuring devices in dams still use traditional methods such as rulers, and the operation of water gates is still done manually. An Internet of Things (IoT)-based water level monitoring system can replace this conventional method. In this system, the HC-SR04 ultrasonic sensor is used to measure the distance between the water surface and the sensor, and to monitor it in real time. Data obtained from the sensor is then sent via the internet to the Blynk application, which allows remote monitoring. The research method using a prototype includes needs analysis, rapid design, prototyping, evaluation, refinement, and implementation. The results of this study are an Internet of Things-based water level monitoring system equipped with water gate automation and internet-based remote control, making it easier for dam operators to work more efficiently and automatically. This system is also equipped with an alarm feature that will sound when the water level reaches a certain limit as a form of early warning.